Examining Service Learning as an Approach to Intensify International Students’ Multicultural Understanding - Idrus, Faizah; Halim, A., Syakirah (Journal of International Students, 2023)
The purpose of this investigation was to identify, examine, and analyse the opinions of four international postgraduate students who embarked on a service-learning project required by the course taken in Semester 2, 2021/2022. It included engaging in community service, connection to their academic endeavours, reporting the outcomes, critical reflection, and reciprocity. Choral speaking activities were selected as the tool for their engagement with children in the community. The qualitative approach was chosen as the research design, employing in-depth semi-structured interviews. The findings pointed to the beneficial aspects of service-learning which include: (1) enhances multicultural understanding; (2) improves civic involvement; (3) acknowledges that academic work has real-world importance; and (4) promotes language learning as well as reciprocity, that need to be improved.